COMPARATIVE STUDY ON RING, ROTOR AND AIR-JET SPUN YARN - Sharif Ahmed; Md. Syduzzaman; Md. Sultan Mahmud; S.M. Ashique; Mohammad Mahbubur Rahman (European Scientific Journal, ESJ, 2015)
Although ring spinning is the universal spinning system but main limitation of this system is its limited spindle speed which causes lower production rate. Now-a-days spinners are trying to finding out various alternative spinning systems among which only rotor and air-jet has established market value. So it is very important for spinners to find out a suitable one according to end use and others economic aspects. Ring, Rotor and Air-jet spinning systems provide yarn with different structures and properties. Each system has its advantages and limitations in terms of technical feasibility and economic viability. We have produced 20's Ne, 100% cotton yarn from the above systems and their properties are tested by UT5 and lea strength tester. The main object of the project is to study the yarn properties (Um%, CVm%, Imperfection, Hairiness etc) of ring, rotor and air-jet spun yarn and compare among them. We observed how yarn properties are changed with the change of process. We analyzed the various yarn properties by the graphical representation.